Study on the intellectual ability of children in schools in Lima (Conclusion) - Chueca, Felipe (1920)
In order to obtain more data from the study undertaken in children in some of our schools; send print a single ballot, which allowed us to relate the mind to age, race, sex, social status, housing, birth and intelligence appreciated by teachers. We divided these ballots into five boxes, one for each of the reagents to the test consist of and we have considered for each reagent required to record the test content divisions, time of execution, the result and the peculiar observations each case, the test development suggested to us, and it seemed to us interesting to note. Since the tests for each age consist of five items, we had the idea to filial as accurately as possible the degree of intelligence, considering the total of her as the unit, splitting it into 10/10, corresponding to each item the value of two tenths.